Contralateral effect in progression and recovery of lens‐induced myopia in mice. (17th March 2023) - Ma, Ziyan; Jeong, Heonuk; Yang, Yajing; Jiang, Xiaoyan; Ikeda, Shin‐ichi; Negishi, Kazuno; Kurihara, Toshihide; Tsubota, Kazuo
Abstract: Purpose: Apart from genetic factors, recent animal studies on myopia have focused on localised mechanisms. In this study, we aimed to examine the contralateral effects of monocular experimental myopia and recovery, which cannot be explained by a mere local mechanism. Methods: One eye of 3‐week‐old C57BL/6 male mice was fitted with a −30 dioptre (D) lens. The mice were distributed into two groups based on different conditions in the contralateral eye: either no lens (NLC) ( n  = 10) or a Plano lens on the contralateral eye (PLC) group ( n  = 6). Mice receiving no treatment on either eye were set as a control group ( n  = 6). Lenses were removed after 3 weeks of myopia induction. All mice were allowed to recover for 1 week in the same environment. Refractive status, axial length (AL) and choroidal thickness were measured before myopia induction, after 1 and 3 weeks of lens wear and after 1 week of recovery. Results: One week after removing the lenses, complete recovery was observed in the eyes that wore the −30 D lenses. In both the PLC and NLC groups, the refractive status showed a myopic shift after lens removal. Additionally, the choroid was significantly thinned in these eyes. The −30 D wearing eye showed a significant increase in AL after 3 weeks of lens wear. While the AL of the −30 D wearing eye ceased to grow after the lens was removed, the AL in the PLC and NLC contralateral eyes increased, and the binocular ALs gradually converged. Conclusions: Recovery of lens‐induced myopia was observed in mouse models. In the fellow eyes, the effects, including thinning of the choroid and changes in refractive status, were triggered by contralateral visual cues.